Interactive effect of elevated [CO2] and temperature on the photosynthetic process, anti-oxidative properties, and grain yield of rice - Dwivedi, Sharad K.; Kumar, Santosh; Mishra, Janki S.; Prakash, Ved; Rao, Karnena K.; Bhatt, Bhagwati P.; Srivastava, Ashish K. (Wiley, 2022)
The simultaneous increase of carbon dioxide and temperature causes significant changes in rice physiology and production, but limited studies have been performed in the past to examine the interactive effect of these two key variables on lipid peroxidation, anti‐oxidative properties, gas exchange parameters, and grain yield of rice. Thus, an experiment was conducted by growing two rice genotypes (IR83376‐B‐B‐24–2 and IR64) inside field‐based open‐top chambers (OTCs) with two levels of [CO2] (ambient and elevated; (500±25 ppm) and temperature (ambient and ambient+2°C) in order to determine their simultaneous effect on lipid peroxidation (thio‐barbituric acid substances, TBARS), anti‐oxidant properties (catalase, CAT and superoxide dismutase, SOD), gas exchange parameters (PN rate, gs, E), WUE and grain yield during the kharif seasons. Our study showed that under simultaneous elevation (CO2 and temperature), the activity of CAT and SOD were improved. CAT showed significant alterations in activity which was detected for genotype IR83376‐B‐B‐24–2 (twelve‐fold increase) under elevated temperature compared to ambient temperature. SOD activity was decreased by 35.1 and 35.7% with elevated [CO2] while it increased under elevated temperature by 103.6 and 41.1% in IR83376‐B‐B‐24–2 and IR64, respectively. No significant difference in TBARS content was observed under combined elevation of both [CO2] and temperature, as compared to ambient conditions. However, elevation in temperature by 2°C led to a reduction in photosynthetic rate and WUE but increased the rate of transpiration, CAT and SOD activity. Grain yield was also improved under elevated [CO2] while elevated temperature has negative impact on grain yield. Thus, the findings suggest that there are differential biochemical (TBARS, CAT, and SOD) and physiological (PN rate, gs, E, and WUE) responses of rice towards predicted climatic conditions. This study represents the significant findings on the anti‐oxidant defence mechanism in rice under combined elevated [CO2] and temperature levels. Furthermore, the genotypic differences observed in terms of photosynthesis mechanism and ROS scavenging system imply that it is possible to breed varieties that will be more suited for future rice production scenarios.